PRELIMINARY PHARMACOLOGICAL SCREENING OF MICROCOCCA MERCURIALI (L.) BENTH. LEAVES EXTRACTS FOR WOUND HEALING ACTIVITY - SINGH, RENU; LODHI, SANTRAM (International Journal of Current Pharmaceutical Research, 2026)
Objective: Wound healing is a complex physiological process that requires a series of steps, each with several factors to come to completion. The objective of present study was to screen different extracts of Micrococca mercurialis (L.) Benth. leaves for wound healing activity using incision and excision wound model in experimental animals. Methods: Different extracts of Micrococca mercurialis leaves were obtained by extraction with petroleum ether, chloroform, acetone, ethyl acetate, methanol and water. All these extracts were tested for detection of phytochemical constituents using different chemical test qualitatively. Preliminary wound healing activity was tested using incision and excision wound models and observed tensile strength of wound tissue in incision wound model. Wound contraction and biochemical estimation from wound tissue were observed in excision wound model. Results: Results of present study was confirmed that methanol extract of Micrococca mercurialis leaves was showed higher tensile strength significantly (P<0.05) in comparison to the control group of animals. Hydroxyproline content and protein content were found significant (P<0.05) greater than the other extracts and standard marketed formulation (Povidone-Iodine ointment). Conclusion: In conclusion, the potent wound healing effect of Micrococca mercurialis leaves extract may be attributed by the presence of phenolic and flavonoids components in the extract. Further detail study is required to explore the mechanism behind the healing effect and specific component responsible for activity.